THE STUDENTS’ PERCEPTION OF WHATSAPP MESSENGER AS E-LEARNING FOR ENGLISH LANGUAGE IN NINTH GRADE OF SMP YLPI P MARPOYAN - Feni Febriana; Lusi Septari; Maya Dwi Sukma Fatania; Tisa Anggraini (Journal on Studies in English Language Teaching (JOSELT), 2023)
The perception of WhatsApp as an E-Learning is expected to simplify the students to learn English because WhatsApp has many features that could help students in learning. However, students have different feelings, opinion, feedback and perception about the use of WhatsApp as an E-Learning. The aim of this research is to find out and analyze the students’ perceptions of using WhatsApp as an E-Learning, namely the feeling and the response from the students in learning. This study used quantitative research and the researcher used questionnaire to collect the data. The questionnaire was arranged using Likert Scale. The result of this study shows that the factors which influence the students’ perception of WhatsApp as an E-Learning in SMP YLPI P MARPOYAN are the perceiver consisting of attitudes, motives, experience, and expectation. The target consists of motion, sounds. The situation consists of time, and work setting. The students’ attitudes of using WhatsApp in grade 9 of SMP YLPI P MARPOYAN display the attitudes for the cognitive and affective is contain positives response and feeling.